Pengaruh Gaya Kepemimpinan Dan Kompensasi Terhadap Kinerja Karyawan Pada PT Khadimu Agmindori Unggul - Muhamad Irfani Aulia Irsyad; Lestari, Tri (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
This study explains leadership style and compensation with the aim of knowing the influence of leadership style and compensation on employee performance. By utilizing census techniques, the research sample used was 70 people. This study utilized the multiple regression analysis method and was processed using SPSS version 25. The test results proved that: (1) leadership style does not have a positive and significant partial effect on employee performance, but compensation has a positive and significant partial effect on employee performance; (2) Simultaneously, the results obtained regarding leadership and compensation have a positive and significant effect on employee performance